A 7-14 μm band DLC / AR infrared germanium window sheet on a germanium substrate and a preparation method thereof
By placing a single-layer DLC film on the front and AR film on the back of the germanium window sheet, the film system structure is simplified, the transmittance and durability of the germanium window sheet is improved, and the problem of insufficient durability caused by the multi-layer film structure in the prior art is solved.
Patent Information
- Application Number
- CN202410266771.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-08
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-03-08
AI Technical Summary
The existing germanium window sheets are coated with multi-layer film structures on both the front and back sides of the substrate, resulting in increased filmmaking time and cost, and the firmness between the film layers is difficult to control and insufficient durability.
A single crystal germanium sheet is used as the substrate, a single layer DLC film is plated on the front and an AR film is plated on the back. The AR film film structure is: single crystal germanium substrate/0.116H/3.091M/0.296L/0.976M/0.699L/0.689I/0.674H/air.
A high transmittance (≥89%) in the 7-14μm band range is achieved, and the durability of the germanium window sheet is improved, suitable for harsh environments, and the preparation cost and time are reduced.
Smart Images

Figure CN118363094B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of optical materials, and in particular relates to a 7-14 μm band DLC / AR infrared germanium window sheet on a germanium substrate and a preparation method thereof. Background Art
[0002] Germanium (Ge) single crystal is a high-refractive-index semiconductor material with excellent performance. It has a diamond structure and good transparency in the infrared band. Germanium is insoluble in water and has stable chemical properties. Its refractive index n≈4.0 in the transmission wavelength range and the dispersion is very small. The transmission wavelength range is 1.8-25μm. It is an excellent infrared material and one of the preferred optical materials for medium-wave and long-wave infrared optical elements and windows. It is widely used in the manufacture of infrared lenses, windows, prisms, lenses, etc. However, due to the limitations of the physical and chemical properties of germanium (Ge) single crystals themselves, the bonding force between the film system and the substrate, and between the film layers is poor, especially the commonly used low-refractive-index materials are soft, easy to absorb moisture, and have poor mechanical properties, so that the multi-layer anti-reflection film cannot withstand harsh environments such as damp heat, salt spray, mold and moderate friction.
[0003] After the germanium window is anti-reflective coated, the common application spectral range is 3-5μm and 8-14μm. With the rapid development of infrared optical systems, the demand for wide-bandwidth infrared germanium windows is becoming more and more urgent.
[0004] The prior art has a publication number of CN108627889B, which discloses a germanium-based wide-spectrum infrared anti-reflection optical window. The infrared anti-reflection optical window anti-reflection film uses germanium (Ge), zinc sulfide (ZnS) and ytterbium fluoride (YbF 3 ) is a long-wave infrared antireflection film on a germanium substrate with film materials of different refractive indices. Its structure is: a positive film system is deposited on one side of the substrate, and a reverse film system with the same structure is deposited on the other side of the substrate. Using specific process conditions such as ion source assisted deposition and appropriate substrate baking temperature, 8 layers of irregular film layers are deposited on the two surfaces of the substrate respectively. The antireflection film element can have a good light transmission effect in the range of 7.5 to 14.0 μm, with an average transmittance of > 96%.
[0005] Although this method has a high overall transmittance, the problem is that the germanium window is coated with a multi-layer film structure on both sides of the substrate. The multi-layer complex film structure not only increases the time and cost of film making, but also makes it difficult to control the firmness between the film layers, resulting in greater concerns about the durability of the resulting germanium window. Summary of the invention
[0006] In order to overcome the problems existing in the background technology, the purpose of the present invention is to provide a germanium substrate 7-14μm band DLC / AR infrared germanium window and a preparation method thereof. The germanium window in the present application has a simpler film structure, significantly reduced number of film layers, better durability, and faster and more efficient preparation, thereby reducing the preparation cost while ensuring a higher transmittance.
[0007] To achieve the above object, the present invention is implemented through the following technical solutions:
[0008] A 7-14 μm band DLC / AR infrared germanium window with a germanium substrate, which uses a single crystal germanium sheet as a substrate, with DLC films coated on the front and back sides of the substrate, and AR films coated on the back side;
[0009] The AR film system structure is: single crystal germanium substrate / 0.116H / 3.091M / 0.296L / 0.976M / 0.699L / 0.689I / 0.674H / air;
[0010] In the formula, H represents a ZnS film with an optical thickness of λ0 / 4; M represents a Ge film with an optical thickness of λ0 / 4; L represents a ZnSe film with an optical thickness of λ0 / 4; I represents a YbF film with an optical thickness of λ0 / 4 3 film layer; λ0 is the central wavelength; the numbers before H, M, L and I are the thickness proportional coefficients of the film layer.
[0011] The method for preparing the above-mentioned DLC / AR infrared germanium window sheet in the 7-14 μm band on a germanium substrate comprises the following steps:
[0012] (1) DLC film coating: A single-layer DLC film is coated on the front side of a single-crystal germanium wafer using a hard carbon film coating machine;
[0013] (2) AR coating: Using the DLC-coated germanium sheet as the substrate, the first ZnS film layer, the first Ge film layer, the first ZnSe film layer, the second Ge film layer, the second ZnSe layer, the first YbF film layer are coated on the reverse side of the sheet in sequence from the inside to the outside. 3 layer, and the second ZnS layer.
[0014] Optionally, in the step (1), before coating the single crystal germanium wafer as the substrate, the single crystal germanium wafer is ion bombarded and cleaned in a hard carbon coating machine, the RF power during bombardment cleaning is 400W, the time is 450s, the auxiliary gas used is argon, the argon purity is ≥99.999%, the argon filling flow rate is 70sccm, the VF plate bias is 500-650 during the cleaning bombardment process, the RF reflection power is 0-10W, and the temperature in the vacuum chamber is controlled to be 100-110°C at the end of cleaning.
[0015] Optionally, in the step (1), when the single crystal germanium wafer is used as the substrate for coating, the RF power supply power is 800W, during the film deposition process, the VF plate bias is 530-540, the RF reflection power is 0-2W, the deposition time is 1437s, and the film thickness after deposition is 1331nm.
[0016] Optionally, in the step (2), before coating, a Hall ion source is used for ion bombardment cleaning for 450s, wherein the ion source anode voltage is 200V, the anode current is 0.8A, the emitter current is 2A, the maintaining level voltage is 20V, and the maintaining level current is 1500mA; during the coating process, a Hall ion source is used to assist the coating, wherein the ion source anode voltage is 100V, the anode current is 0.6A, and the emitter current is 1.5A; after coating, a Hall ion source is used to bombard the surface of the film layer, wherein the ion source anode voltage is 100V, the anode current is 0.6A, and the emitter current is 1.5A.
[0017] Optionally, in step 2, the ZnS film layer is evaporated by resistance heating evaporation, the evaporation boat is a bottom cover with a gap at the edge and a molybdenum boat with a 1mm evaporation aperture upper cover, and the ZnS is automatically pre-melted to a molten state before deposition, and the pre-melting gradient is 400A for 150s, 500A for 200s, and 580A for 120s, respectively. During deposition, the resistance evaporation current is 560±10A, and the ZnS film deposition rate is 0.8nm / s. .
[0018] Optionally, in the step 2, the ZnSe film layer is evaporated by resistance heating evaporation. The evaporation boat is a bottom cover with a gap at the edge and a molybdenum boat with a top cover with an evaporation aperture of 1 mm. Before deposition, the ZnSe is automatically pre-melted to a molten state. The pre-melting gradients are 360A for 150s, 440A for 170s, and 500A for 100s. The resistance evaporation current during deposition is 480±10A, and the ZnS film deposition rate is 0.6nm / s.
[0019] Optionally, in step 2, YbF 3 The film layer was deposited by resistance heating evaporation. The evaporation boat was a molybdenum boat with a 0.6mm evaporation aperture cover. 3 Automatic pre-melting to molten state, the pre-melting gradient is 800A for 200s, 1000A for 300s, 1200A for 200s, the steam resistance current is 1100±10A during deposition, YbF 3 The film deposition rate is 0.6 nm / s.
[0020] Optionally, in the step 2, the Ge film layer is evaporated by electron beam evaporation. Before deposition, Ge is automatically pre-melted to a molten state. The pre-melting gradients are 100mA for 60s, 150mA for 50s, and 220mA for 100s. During pre-melting, the electron beam spot increases from small to small and decreases from small to small until the pre-melting is completed. During deposition, the electron beam current is 200±10mA, the electron beam spot size is 1mm, and the Ge film deposition rate is 0.3nm / s.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The DLC / AR infrared germanium window piece with a germanium substrate and a 7-14μm band provided by the present invention has only a single-layer DLC film coated on the front side and an AR film coated on the back side; the AR film system structure is: single crystal germanium substrate / 0.116H / 3.091M / 0.296L / 0.976M / 0.699L / 0.689I / 0.674H / air. Compared with the germanium window piece with a 7.5-14.0μm band in the prior art, which has a structure with eight layers of film only on one side of the substrate; the film system structure in the present application is simpler, consisting of a single-layer DLC film and an AR film, and the AR film system has only a seven-layer structure, and the film layers on the front and back sides add up to only eight layers; the significant reduction of the film layer structure can not only effectively save film system materials, but also save a lot of coating time, and the entire coating process is more time-saving and labor-saving.
[0023] 2. The 7-14μm band DLC / AR infrared germanium window film on the germanium substrate prepared in this application achieves an average transmittance of ≥89% in the 7-14μm band. At the same time, due to the change in the film structure, it has strong durability in harsh environments. The friction resistance, corrosion resistance, high temperature resistance and surface hardness experiments of the germanium window film surface show that it has strong environmental adaptability and is therefore suitable for industrial production.
[0024] 3. The key point of the preparation of the DLC / AR infrared germanium window in the 7-14μm band on the germanium substrate of the present application lies in the special selection of the film system structure on the one hand, and in the control of the corresponding film layer structure and thickness through the selected special film system structure on the other hand. Ultimately, the film layer is greatly reduced, the preparation efficiency is improved, the production cost is reduced, and the infrared germanium window has a good transmittance and strong environmental adaptability. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is the transmittance spectrum of DLC / AR infrared germanium window in the 7-14μm band on germanium substrate;
[0026] Figure 2 This is the transmittance spectrum of the DLC-coated infrared germanium window;
[0027] Figure 3 This is the transmittance spectrum of the AR-coated infrared germanium window;
[0028] Figure 4 It is a strong adhesion test of infrared germanium window with DLC / AR composite coating;
[0029] Figure 5 It is a wet heat test for infrared germanium windows with DLC / AR composite coating;
[0030] Figure 6 It is the salt spray test of infrared germanium window with DLC / AR composite coating;
[0031] Figure 7 It is a heavy friction test of infrared germanium window with DLC / AR composite coating;
[0032] Figure 8 It is a special high temperature test for infrared germanium windows with DLC / AR composite coating. DETAILED DESCRIPTION
[0033] In order to make the objectives, technical solutions and beneficial effects of the present invention clearer, the preferred embodiments of the present invention will be described in detail below to facilitate understanding by technicians.
[0034] Example 1
[0035] A method for preparing a 7-14 μm band DLC / AR infrared germanium window on a germanium substrate comprises the following operations:
[0036] Front DLC coating
[0037] (1) Precision grinding and polishing single crystal germanium to obtain a single crystal germanium wafer;
[0038] (2) The single crystal germanium wafer is ion cleaned and bombarded in a hard carbon coating machine, wherein the RF power during cleaning bombardment is 400W, the time is 450s, the auxiliary gas used is argon, the purity of argon is ≥99.999%, the argon filling flow rate is 70sccm, the VF plate bias during cleaning bombardment is 500-650, the RF reflection power is 0-10W, and the temperature in the vacuum chamber is controlled to be 100-110°C at the end of cleaning;
[0039] (3) A single-layer DLC film was coated on a single crystal germanium wafer using a hard carbon film coating machine, with a central wavelength of 10.6 μm; the vacuum condition for coating was ≤ 0.001 Pa; the auxiliary gases used during coating were argon and n-butane (C 4 H 10); the purity of the auxiliary gas argon used is ≥99.999%, and the argon filling flow rate is 35sccm; the purity of the auxiliary gas n-butane used is ≥99.999%, and the argon filling flow rate is 50sccm; the vacuum degree during coating is 10Pa; the RF power supply power during coating is 800W, and during the film deposition process, the VF plate bias is 530-540, the RF reflection power is 0-2W, the deposition time is 1437s, and the film thickness after deposition is 1331nm.
[0040] AR coating on the reverse side
[0041] (1) The constant temperature before coating and the coating temperature are both 160°C, the constant temperature time is ≥35min, and the vacuum condition for coating is ≤0.0006Pa; before coating, the germanium sheet coated with DLC film on one side is cleaned and bombarded by Hall ion source for 450s, the ion source anode voltage is 200V, the anode current is 0.8A, the emission level current is 2A, the holding level voltage is 20V, and the holding level current is 1500mA;
[0042] (2) In an infrared anti-reflection film coating machine, a germanium sheet coated with a DLC film on one side is used as a substrate to coat the first ZnS film layer, the first Ge film layer, the first ZnSe film layer, the second Ge film layer, the second ZnSe layer, the first YbF film layer, and the second ZnS film layer. 3 layer, and the second ZnS layer; during the coating process, a Hall ion source is used to assist the coating, wherein the ion source anode voltage is 100V, the anode current is 0.6A, and the emitter current is 1.5A;
[0043] The ZnS film layer was deposited by resistance heating evaporation. The evaporation boat was a bottom cover with a gap at the edge and a molybdenum boat with a 1mm evaporation aperture top cover. Before deposition, the ZnS was automatically pre-melted to a molten state. The pre-melting gradient was 400A for 150s, 500A for 200s, and 580A for 120s. The resistance evaporation current during deposition was 560±10A, and the ZnS film deposition rate was 0.8nm / s.
[0044] The ZnSe film layer was deposited by resistance heating evaporation. The evaporation boat was a bottom cover with a gap at the edge and a molybdenum boat with a 1mm evaporation aperture top cover. Before deposition, the ZnSe was automatically pre-melted to a molten state. The pre-melting gradient was 360A for 150s, 440A for 170s, and 500A for 100s. The resistance evaporation current during deposition was 480±10A, and the ZnS film deposition rate was 0.6nm / s.
[0045] Yb 3 The film layer was deposited by resistance heating evaporation. The evaporation boat was a molybdenum boat with a 0.6mm evaporation aperture cover. 3Automatic pre-melting to molten state, the pre-melting gradient is 800A for 200s, 1000A for 300s, 1200A for 200s, the steam resistance current is 1100±10A during deposition, YbF 3 The film deposition rate is 0.6nm / s;
[0046] The Ge film layer is deposited by electron beam evaporation. Before deposition, Ge is automatically pre-melted to a molten state. The pre-melting gradient is 100 mA for 60 s, 150 mA for 50 s, and 220 mA for 100 s. During pre-melting, the electron beam spot increases from small to small and decreases from small to small until the pre-melting is completed. During deposition, the electron beam current is 200±10 mA, the electron beam spot size is 1 mm, and the Ge film deposition rate is 0.3 nm / s.
[0047] (3) After the coating is completed, the surface of the film layer is bombarded with a Hall ion source, where the ion source anode voltage is 100 V, the anode current is 0.6 A, and the emitter current is 1.5 A.
[0048] During the coating process, the film deposition rate and film thickness are controlled by a quartz crystal controller to obtain an infrared germanium window with a 7-14μm DLC / AR composite coating. The transmittance spectrum is shown in Figure 1 shown.
[0049] Example 2
[0050] In this embodiment, only DLC coating is performed on a single crystal germanium wafer, and the preparation method of the DLC coated infrared germanium window wafer includes the following operations:
[0051] DLC film coating
[0052] (1) Precision grinding and polishing single crystal germanium to obtain a single crystal germanium wafer;
[0053] (2) The single crystal germanium wafer is ion cleaned and bombarded in a hard carbon coating machine, wherein the RF power during cleaning bombardment is 400W, the time is 450s, the auxiliary gas used is argon, the purity of argon is ≥99.999%, the argon filling flow rate is 70sccm, the VF plate bias during cleaning bombardment is 500-650, the RF reflection power is 0-10W, and the temperature in the vacuum chamber is controlled to be 100-110°C at the end of cleaning;
[0054] (3) A single-layer DLC film was coated on a single crystal germanium wafer using a hard carbon film coating machine, with a central wavelength of 10.6 μm; the vacuum condition for coating was ≤ 0.001 Pa; the auxiliary gases used during coating were argon and n-butane (C 4 H 10); the purity of the auxiliary gas argon used is ≥99.999%, and the argon filling flow rate is 35sccm; the purity of the auxiliary gas n-butane used is ≥99.999%, and the argon filling flow rate is 50sccm; the vacuum degree during coating is 10Pa; the RF power supply power during coating is 800W, and during the film deposition process, the VF plate bias is 530-540, the RF reflection power is 0-2W, the deposition time is 1437s, and the film thickness after deposition is 1331nm.
[0055] During the coating process, the film deposition rate and film thickness are controlled by a quartz crystal controller to obtain a DLC-coated infrared germanium window. The transmittance spectrum is shown in Figure 2 shown.
[0056] Example 3
[0057] In this embodiment, only AR coating is performed on a single crystal germanium wafer, and the method for preparing the AR coated infrared germanium window wafer includes the following operations:
[0058] AR coating
[0059] (1) The constant temperature before coating and the coating temperature are both 160°C, the constant temperature time is ≥35min, and the vacuum condition for coating is ≤0.0006Pa; before coating, the germanium sheet coated with DLC film on one side is cleaned and bombarded by Hall ion source for 450s, the ion source anode voltage is 200V, the anode current is 0.8A, the emission level current is 2A, the holding level voltage is 20V, and the holding level current is 1500mA;
[0060] (2) In an infrared anti-reflection film coating machine, a germanium sheet coated with a DLC film on one side is used as a substrate to coat the first ZnS film layer, the first Ge film layer, the first ZnSe film layer, the second Ge film layer, the second ZnSe layer, the first YbF film layer, and the second ZnS film layer. 3 layer, and the second ZnS layer; during the coating process, a Hall ion source is used to assist the coating, wherein the ion source anode voltage is 100V, the anode current is 0.6A, and the emitter current is 1.5A;
[0061] The ZnS film layer was deposited by resistance heating evaporation. The evaporation boat was a bottom cover with a gap at the edge and a molybdenum boat with a 1mm evaporation aperture top cover. Before deposition, the ZnS was automatically pre-melted to a molten state. The pre-melting gradient was 400A for 150s, 500A for 200s, and 580A for 120s. The resistance evaporation current during deposition was 560±10A, and the ZnS film deposition rate was 0.8nm / s.
[0062] The ZnSe film layer was deposited by resistance heating evaporation. The evaporation boat was a bottom cover with a gap at the edge and a molybdenum boat with a 1mm evaporation aperture top cover. Before deposition, the ZnSe was automatically pre-melted to a molten state. The pre-melting gradient was 360A for 150s, 440A for 170s, and 500A for 100s. The resistance evaporation current during deposition was 480±10A, and the ZnS film deposition rate was 0.6nm / s.
[0063] Yb 3 The film layer was deposited by resistance heating evaporation. The evaporation boat was a molybdenum boat with a 0.6mm evaporation aperture cover. 3 Automatic pre-melting to molten state, the pre-melting gradient is 800A for 200s, 1000A for 300s, 1200A for 200s, the steam resistance current is 1100±10A during deposition, YbF 3 The film deposition rate is 0.6nm / s;
[0064] The Ge film layer is deposited by electron beam evaporation. Before deposition, Ge is automatically pre-melted to a molten state. The pre-melting gradient is 100 mA for 60 s, 150 mA for 50 s, and 220 mA for 100 s. During pre-melting, the electron beam spot increases from small to small and decreases from small to small until the pre-melting is completed. During deposition, the electron beam current is 200±10 mA, the electron beam spot size is 1 mm, and the Ge film deposition rate is 0.3 nm / s.
[0065] (3) After the coating is completed, the surface of the film layer is bombarded with a Hall ion source, where the ion source anode voltage is 100 V, the anode current is 0.6 A, and the emitter current is 1.5 A.
[0066] During the coating process, the film deposition rate and film thickness are controlled by a quartz crystal controller to obtain an AR coated infrared germanium window. The transmittance spectrum is shown in Figure 3 shown.
[0067] Example 4: Film test of infrared germanium window with DLC / AR composite coating
[0068] (1) Strong adhesion test
[0069] Figure 4 The strong adhesion test of the infrared germanium window sheet of DLC / AR composite coating prepared in Example 1 is as follows: Figure 4 As shown, a 2cm wide transparent tape with a peel strength of not less than 6N / cm was firmly adhered to the surface of the film layer, and then it was quickly pulled up with a force perpendicular to the surface of the film layer. The surface was cleaned and tested 10 times. After the test, no film falling off, wrinkling or cracking occurred.
[0070] (2) Wet heat test
[0071] Figure 5 It is a wet heat test of infrared germanium window with DLC / AR composite coating, such as Figure 5 As shown, the lens was placed in a wet heat box, the temperature was raised to 50°C, and then the humidity was adjusted to 95%-100% and kept for 24 hours. The lens was taken out, its surface was cleaned and the film was pulled 10 times. After the test, no film shedding, wrinkling or cracking occurred.
[0072] (3) Moderate friction test
[0073] The moderate friction test is carried out within one hour after the wet heat test. Use a handheld wiper (pumice-rubber friction head, the friction head is composed of high-quality rubber and pumice filler, Rockwell hardness is 75±5 degrees, the rubber weight is 45% to 55% of the filler weight), wrapped with a clean and dry degreased cloth with a laminate thickness of 6 layers, maintain a vertical pressure of 4.9N, rub the film layer, the stroke length is about 2 times the diameter of the friction head, rub 50 times (25 back and forth) along the same track, clean its surface and pull the film 10 times, and no film shedding, wrinkling, or cracking occurs after the test.
[0074] (4) High and low temperature test
[0075] The test sample was placed in a high and low temperature box, and the temperature was lowered from room temperature to -40±2℃. The temperature change rate was no more than 2℃ / min. The temperature was maintained for 12 hours. The test sample was taken out, placed at room temperature, and its surface was cleaned. The film was then pulled 10 times. After the test, no film shedding, wrinkling or cracking occurred.
[0076] Place the test sample in a high and low temperature box, raise the temperature from room temperature to 70±2℃, with the temperature change rate not exceeding 2℃ / min, and maintain for 12 hours. Take out the test sample, place it at room temperature, clean its surface and pull the film 10 times. After the test, no film shedding, wrinkling or cracking occurs.
[0077] (5) Solvent resistance and erasure resistance test
[0078] The test sample was immersed in trichloroethylene (AR grade), acetone (AR grade) and anhydrous ethanol (AR grade) at a temperature of 16-32°C for 10 minutes each. After being taken out of each solvent, the solvent should be fully evaporated before being put into the next solvent. Finally, after being taken out of anhydrous ethanol and evaporated, the surface was cleaned with an absorbent cloth dipped in anhydrous ethanol and the film was pulled 10 times. After the test, no film shedding, wrinkling or cracking occurred.
[0079] (6) Salt spray test:
[0080] Figure 6 It is the salt spray test of infrared germanium window with DLC / AR composite coating, such as Figure 6As shown, in a salt spray box at a temperature of 35±2℃, a sodium chloride solution with a concentration of 4.9% to 5.1% and a pH value of 6.5 to 7.2 was continuously sprayed for 24 hours, and the surface was cleaned and then the film was pulled 10 times. After the test, no film shedding, wrinkling or cracking occurred.
[0081] (7) Heavy friction test
[0082] Figure 7 It is a heavy friction test of infrared germanium window with DLC / AR composite coating, such as Figure 7 As shown, the moderate friction test is carried out within one hour after the wet heat test. Use a handheld wiper (pumice-rubber friction head, the friction head is composed of high-quality rubber and pumice filler, Rockwell hardness is 75±5 degrees, the rubber weight is 45% to 55% of the filler weight), wrapped with a clean and dry degreased cloth with a laminate thickness of 6 layers, maintain a vertical pressure of 30N, rub the film layer, the stroke length is about 2 times the diameter of the friction head, rub 50 times (25 back and forth) along the same track, clean its surface and pull the film 10 times, and no film shedding, wrinkling, or cracking occurs after the test.
[0083] (8) Special high temperature
[0084] Figure 8 It is a special high temperature test for infrared germanium windows with DLC / AR composite coating, such as Figure 8 As shown, after the film layer was subjected to a high temperature of 300℃-400℃ for 2h (the temperature change rate shall not exceed 5℃ / min), no film layer shedding, wrinkling or cracking occurred after the test.
[0085] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.
Claims
1. A 7-14 μm band DLC / AR infrared germanium window on a germanium substrate, characterized in that: The single crystal germanium wafer is used as the substrate, the front side of the substrate is coated with a DLC film, and the back side is coated with an AR film; The AR film system structure is: single crystal germanium substrate / 0.116H / 3.091M / 0.296L / 0.976M / 0.699L / 0.689I / 0.674H / air; Wherein, H represents a ZnS film layer with an optical thickness of λ0 / 4; M represents a Ge film layer with an optical thickness of λ0 / 4; L represents a ZnSe film layer with an optical thickness of λ0 / 4; I represents a YbF3 film layer with an optical thickness of λ0 / 4; λ0 is the center wavelength; the numbers before H, M, L and I are all thickness proportional coefficients of the film layers.
2. A method for preparing a 7-14 μm band DLC / AR infrared germanium window sheet on a germanium substrate as claimed in claim 1, characterized in that: The following steps are involved: (1) DLC film coating: A single-layer DLC film is coated on the front side of a single-crystal germanium wafer using a hard carbon film coating machine; (2) AR film coating: Using the DLC-coated germanium sheet as the substrate, an infrared anti-reflection film coating machine is used to coat the first ZnS film layer, the first Ge film layer, the first ZnSe film layer, the second Ge film layer, the second ZnSe layer, the first YbF3 layer, and the second ZnS layer on its reverse side from the inside to the outside.
3. The preparation method according to claim 2, characterized in that: In the step (1), before coating the single crystal germanium wafer as the substrate, the single crystal germanium wafer is ion bombarded and cleaned in a hard carbon coating machine. The RF power supply power during bombardment cleaning is 400W, the time is 450s, the auxiliary gas used is argon, the argon purity is ≥99.999%, the argon filling flow rate is 70sccm, the VF plate bias is 500-650 during the cleaning bombardment process, the RF reflection power is 0-10W, and the temperature in the vacuum chamber is controlled to be 100-110°C at the end of cleaning.
4. The preparation method according to claim 2, characterized in that: In the step (1), when the single crystal germanium wafer is used as the substrate for coating, the RF power supply power is 800W. During the film deposition process, the VF plate bias is 530-540, the RF reflection power is 0-2W, the deposition time is 1437s, and the film thickness after deposition is 1331nm.
5. The preparation method according to claim 2, characterized in that: In the step (2), before coating, a Hall ion source is used for ion bombardment cleaning for 450 seconds, wherein the ion source anode voltage is 200V, the anode current is 0.8A, the emission level current is 2A, the maintenance level voltage is 20V, and the maintenance level current is 1500mA; during the coating process, a Hall ion source is used to assist the coating, wherein the ion source anode voltage is 100V, the anode current is 0.6A, and the emission level current is 1.5A; after coating, the surface of the film layer is bombarded with a Hall ion source, wherein the ion source anode voltage is 100V, the anode current is 0.6A, and the emission level current is 1.5A.
6. The preparation method according to claim 2, characterized in that: In the step 2, the ZnS film layer is evaporated by resistance heating evaporation. The evaporation boat is a molybdenum boat with a bottom cover with a gap at the edge and an upper cover with an evaporation aperture of 1 mm. Before deposition, the ZnS is automatically pre-melted to a molten state. The pre-melting gradients are 400A for 150s, 500A for 200s, and 580A for 120s. The resistance evaporation current during deposition is 560±10A, and the ZnS film deposition rate is 0.8nm / s.
7. The preparation method according to claim 2, characterized in that: In the step 2, the ZnSe film layer is evaporated by resistance heating evaporation. The evaporation boat is a bottom cover with a gap at the edge and a molybdenum boat with a 1mm evaporation aperture upper cover. Before deposition, the ZnSe is automatically pre-melted to a molten state. The pre-melting gradients are 360A for 150s, 440A for 170s, and 500A for 100s. The resistance evaporation current during deposition is 480±10A, and the ZnS film deposition rate is 0.6nm / s.
8. The preparation method according to claim 2, characterized in that: In the step 2, the YbF3 film layer is evaporated by resistance heating evaporation. The evaporation boat is a molybdenum boat with a 0.6 mm evaporation aperture cover. Before deposition, the YbF3 is automatically pre-melted to a molten state. The pre-melting gradients are 800A for 200s, 1000A for 300s, and 1200A for 200s. The resistance evaporation current during deposition is 1100±10A, and the YbF3 film deposition rate is 0.6nm / s.
9. The preparation method according to claim 2, characterized in that: In the step 2, the Ge film layer is evaporated by electron beam evaporation. Before deposition, Ge is automatically pre-melted to a molten state. The pre-melting gradients are 100 mA for 60 s, 150 mA for 50 s, and 220 mA for 100 s. During pre-melting, the electron beam spot increases from small to large and decreases from small to small until the pre-melting is completed. During deposition, the electron beam current is 200±10 mA, the electron beam spot size is 1 mm, and the Ge film deposition rate is 0.3 nm / s.
Citation Information
Patent Citations
A germanium-based broadband infrared anti-reflection optical window
CN108627889B
ZnSe substrate 7.7-9.5micrometer waveband high-durability antireflection film and preparation method
CN112505803A
8-12 [mu] m waveband HD film infrared germanium diaphragm
CN116577850A
Preparation method for plating 3-5 [mu] m DLC (diamond-like carbon) antireflection film on silicon lens substrate
CN116641021A